Cypha norvegica nov. sp. (Coleoptera, Staphylinidae) described from Norway - Ødegaard, Frode; Hanssen, Oddvar (Zootaxa, 2018)
A new staphylinid beetle, Cypha norvegica nov.sp., is described, illustrated and distinguished from similar species within the genus. The type specimens were collected, when swarming, before sunset in an extensively managed grassland in Vågå municipality, Oppland in Norway.